2019
DOI: 10.1097/md.0000000000016941
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival of colorectal cancer by stage at diagnosis

Abstract: Population-based cancer registries (PBCR) participate in epidemiological surveillance and in the evaluation of cancer types by enabling analysis of incidence and survival data over time. The aim of this study was to examine overall survival (OS) in patients with colorectal cancer (CRC) by analyzing data from the Martinique population-based cancer registry between 1993 and 2012. All colorectal cancer cases diagnosed in Martinique between 1993 and 2012 were included. Characteristics of CRC patients were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 14 publications
5
39
1
Order By: Relevance
“…CRC is a multifactorial disease, which is closely linked to genetic predisposition, inflammatory bowel disease (IBD), smoking, alcohol consumption and dietary factors [ 1 , 4 , 5 , 6 ]. More than 50% of CRC patients are diagnosed with advanced disease (stage III and IV) [ 7 , 8 , 9 ]. CRC therapy is essentially based on surgery, radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…CRC is a multifactorial disease, which is closely linked to genetic predisposition, inflammatory bowel disease (IBD), smoking, alcohol consumption and dietary factors [ 1 , 4 , 5 , 6 ]. More than 50% of CRC patients are diagnosed with advanced disease (stage III and IV) [ 7 , 8 , 9 ]. CRC therapy is essentially based on surgery, radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the continuous refinement of the TNM system, T (tumor), N (node), and M (metastasis) staging define the prognosis and patient outcome and play a pivotal role in decision-making for treatment 57 , 58 . Accumulating data underlines the importance of structuring the management of CRC patient's survival by stages at diagnosis and prognostic stratification 59 , 60 . In addition, LNI, NI, distant metastasis, tumor recurrence, and age were prognostic variables in univariate analysis that depicted the associations between these parameters and more aggressive tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram model characterized by mutant genes and clinical indexes to identify high-risk patients with stage III/IV colorectal cancer previously published studies have confirmed that stage III-IV CRC at the time of diagnosis is the main prognostic factor affecting overall survival (4). Accurate pathological staging is of significance for the selection of postoperative therapeutic schemes and clinical research.…”
Section: Introductionmentioning
confidence: 98%